STUDI KASUS GELANDANGAN – PENGEMIS (GEPENG) DI KECAMATAN KUBU KABUPATEN KARANGASEM - Iqbali, Saptono (PIRAMIDA; Vol. 4, No. 1 Juli 2008, 2012)
This research meant to get imago about demographic charateristik and economic social and patternbehavior of gepeng ( loiterer and beggar) especially coming from Muntigunung and Pedahan, Sub-Province Karangasem. This imago addressed to compile program solution of gepeng effectively and efesienby paying attention to potency and constraint solution of gepeng.Result of research indicates that behavior of loiterer and beggar to grow naturally and throughrational idea. Development of behavior of gepeng) is divided to to become three periods, that is beforemount Agung erupts ( 1963), after mount Agung erupts ( 1963 - 1970), and after 1980 an. Initially publicdoes barter activity, then pass into beggar as result of urban community do not want to receive goodsbrought and better gives money as pity taste.Seen from demography characteristic, mostly doing activity of gepeng is mothers and children andgenerally they pertained productive labour and children pertained baby and is including school age .Education of family gepeng in general low and condition of its the economics better relative compared todoing no activity gepeng.Wisdom solution of gepeng is with interest races rural development. Its the strategy is exploit opportunitywhich there have, develops potency owned and as possible lessens the constraints, all can touchrequirement of material and spiritual.
Keywords: poverty, urbanization, norms, behavior.